Enhancement of thermal stability and energy storage capability of flexible Ag nanodot/polyimide nanocomposite films via in situ synthesis. Issue 36 (25th August 2020) - Xing, Shuang; Pan, Zhongbin; Wu, Xiaofeng; Chen, Hanxi; Lv, Xujiao; Li, Peng; Liu, Jinjun; Zhai, Jiwei
Abstract : Composite films with an ultralow filler content of 0.1 vol% Ag-NDs exhibit an excellent high-temperature discharge energy density of 2.56 J cm −3, together with efficiency exceeding 80% at a temperature of 150 °C. Abstract : High-temperature electrostatic capacitors are in urgent demand owing to the rapid development of advanced power electronic applications. However, obtaining polymer films with excellent discharge energy density and efficiency is still a huge challenge under harsh environmental conditions. Here, novel Ag nanodot/polyimide (Ag-ND/PI) nanocomposite films are designed and prepared through an in situ method. The energy storage capability and thermal stability of the PI matrix are significantly improved via loading a small amount of Ag-NDs, owing to the Coulomb-blockade effect and high thermal conductivity. Particularly, a high discharge energy density ( U d ) of 5.16 J cm −3 at 600 MV m −1 is achieved for nanocomposite films with an ultralow filler content of 0.1 vol% Ag-NDs at room temperature, which is 260% higher than that of the pristine PI (2.02 J cm −3 at 450 MV m −1 ). Concurrently, the corresponding nanocomposite films exhibit an excellent high-temperature U d of 2.56 J cm −3, together with efficiency exceeding 80% at a temperature of 150 °C at 400 MV m −1 . Therefore, this research unveils a new method towards high-performance polymer capacitors for high-temperature applications.